2016
DOI: 10.1371/journal.pone.0166532
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reliability of the Kinect Version 2 for Clinical Measurement of Motor Function

Abstract: BackgroundThe introduction of low cost optical 3D motion tracking sensors provides new options for effective quantification of motor dysfunction.ObjectiveThe present study aimed to evaluate the Kinect V2 sensor against a gold standard motion capture system with respect to accuracy of tracked landmark movements and accuracy and repeatability of derived clinical parameters.MethodsNineteen healthy subjects were concurrently recorded with a Kinect V2 sensor and an optical motion tracking system (Vicon). Six differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
163
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(197 citation statements)
references
References 20 publications
(37 reference statements)
10
163
2
4
Order By: Relevance
“…Regarding accuracy for motion tracking, the Kinect is adequate for most scientific purposes, including medical studies on posture and rehabilitation (Clark et al, 2012;Clark et al, 2015;Zhao et al, 2014). In particular, Otte et al (2016) have shown that the Kinect V2 can derive clinical motion parameters with comparable performance to that obtained by a gold standard motion capture system.…”
Section: Virtual Reality Technologiesmentioning
confidence: 92%
“…Regarding accuracy for motion tracking, the Kinect is adequate for most scientific purposes, including medical studies on posture and rehabilitation (Clark et al, 2012;Clark et al, 2015;Zhao et al, 2014). In particular, Otte et al (2016) have shown that the Kinect V2 can derive clinical motion parameters with comparable performance to that obtained by a gold standard motion capture system.…”
Section: Virtual Reality Technologiesmentioning
confidence: 92%
“…Comparable validation results were reported by Capecci et al [34], where for a set of three rehabilitation exercises an average positional RMSE of 3.3 cm (1.3 inch) and an average orientational RMSE of 12.7 degrees were recorded. In [88], Otte et al…”
Section: Vision/depth Camerasmentioning
confidence: 99%
“…These limitations could be reduced with the Kinect V2 since it presents higher‐specification cameras, an improved field of view, image resolution, body tracking algorithms, noise reduction filters and the ability to track more joints and more bodies than its predecessor. A previous study claims that Kinect V2 could be used for clinical measurement of motor function, but there is still the need for outlier detection before the calculation of clinical parameters . Therefore, even though Kinect V2 improves the V1 specifications, it is necessary to apply a model correction to the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study claims that Kinect V2 could be used for clinical measurement of motor function, but there is still the need for outlier detection before the calculation of clinical parameters. 17 Therefore, even though Kinect V2 improves the V1 specifications, it is necessary to apply a model correction to the measurements.…”
mentioning
confidence: 99%